PRAGMATIC FEATURES OF RHETORICAL INTERROGATIVE SENTENCES IN ENGLISH AND UZBEK - Kasimova Nafisa Farkhadovna; Nurillaeva Mavluda (Western European Studies, 2025)
Rhetorical interrogatives are a vital tool in both English and Uzbek for conveying nuanced meanings beyond literal interpretation. This article examines the pragmatic characteristics of rhetorical questions in both languages, highlighting how cultural, social, and linguistic contexts shape their use. The study identifies similarities and differences in form, function, and communicative effects of rhetorical interrogatives, emphasizing the role of intonation, discourse strategies, and pragmatic markers in effective communication. The findings contribute to cross-linguistic understanding and language teaching.
Keywords: Rhetorical questions; pragmatics; English; Uzbek